Mesenchymal stem cell-mediated adipogenic transformation: a key driver of oral squamous cell carcinoma progression - Yiting Shao; Yu Du; Zheng Chen; Lei Xiang; Shaoqin Tu; Yi Feng; Yuluan Hou; Xiaoxing Kou; Hong Ai (Stem Cell Research & Therapy)
Abstract Background Interaction between mesenchymal stem cells (MSCs) and oral squamous cell carcinoma (OSCC) cells plays a major role in OSCC progression. However, little is known about adipogenic differentiation alteration in OSCC-derived MSCs (OSCC-MSCs) and how these alterations affect OSCC growth. Methods MSCs were successfully isolated and cultured from normal gingival tissue, OSCC peritumoral tissue, and OSCC tissue. This included gingiva-derived MSCs (GMSCs), OSCC adjacent noncancerous tissues-derived MSCs (OSCCN-MSCs), and OSCC-MSCs. The adipogenic and osteogenic differentiation capabilities of these cells were evaluated using Oil Red O and Alizarin Red S staining, respectively. OSCC cells were then co-cultured with either OSCC-MSCs or GMSCs to assess the impact on OSCC cell proliferation and migration. Subcutaneous xenograft experiments were conducted in BALB/c-nu mice to further investigate the effects in vivo. Additionally, immunohistochemical staining was performed on clinical samples to determine the expression levels of fatty acid synthase (FASN) and the proliferation marker Ki67. Results OSCC-MSCs exhibited enhanced adipogenic differentiation and reduced osteogenic differentiation compared to GMSCs. OSCC-MSCs significantly increased the proliferation and migration of OSCC cells relative to GMSCs and promoted tumor growth in mouse xenografts. Lipid droplet accumulation in the stroma was significantly more pronounced in OSCC + OSCC-MSCs xenografts compared to OSCC + GMSCs xenografts. Free fatty acids (FFAs) levels were elevated in OSCC tissues compared to normal gingival tissues. Moreover, OSCC-MSCs consistently secreted higher levels of FFAs in condition medium than GMSCs. Knockdown of FASN in OSCC-MSCs reduced their adipogenic potential and inhibited their ability to promote OSCC cell proliferation and migration. Clinical sample analysis confirmed higher FASN expression in OSCC stroma, correlating with larger tumor size and increased Ki67 expression in cancer tissues, and was associated with poorer overall survival. Conclusions OSCC-MSCs promoted OSCC proliferation and migration by upregulating FASN expression and facilitating FFAs secretion. Our results provide new insight into the mechanism of OSCC progression and suggest that the FASN of OSCC-MSCs may be potential targets of OSCC in the future.